Statistics for business and economics - McClave, James T.; Benson, P. George 1946-; Sincich, Terry (Harlow,United Kingdom Pearson Education Limited, 2018)
"Statistics for Business and Economics introduces statistics in the context of contemporary business. Emphasizing statistical literacy in thinking, the text applies its concepts with real data and uses technology to develop a deeper conceptual understanding. Examples, activities, and case studies foster active learning in the classroom while emphasizing intuitive concepts of probability and teaching students to make informed business decisions. The 13th Edition continues to highlight the importance of ethical behavior in collecting, interpreting, and reporting on data, while also providing a wealth of new and updated exercises and case studies."--Provided by publisher.
1. Statistics, Data, and Statistical Thinking2. Methods for Describing Sets of Data3. Probability4. Random Variables and Probability Distributions5. Sampling Distributions6. Inferences Based on a Single Sample: Estimation with Confidence Intervals7. Inferences Based on a Single Sample: Tests of Hypotheses8. Inferences Based on Two Samples: Confidence Intervals and Tests of Hypotheses9. Design of Experiments and Analysis of Variance10. Categorical Data Analysis11. Simple Linear Regression12. Multiple Regression and Model Building13. Methods for Quality Improvement: Statistical Process Control (Available Online)14. Time Series: Descriptive Analyses, Models, and Forecasting (Available Online)15. Nonparametric Statistics (Available Online).
Keywords: Commercial statistics; Economics -- Statistical methods; Statistics